Inflation-linked public debt in emerging economies. (May 2019) - Gomez-Gonzalez, Patricia
Highlights: 23% of emerging markets' local currency (LC) public debt is linked to inflation. For some countries, inflation-linked (IL) rates are 1.2-5pp. lower than LC rates. IL debt issuance is countercyclical and increases amid exchange rate depreciations. IL debt substitutes foreign currency (FC) and non-indexed LC debt. IL debt substitutes FC debt because, during short recessions, IL rates decrease. Abstract: This study reports a set of stylized facts about inflation-linked (IL) public debt in emerging economies. On average, emerging economies issue 23% of their local currency (LC) public debt linked to inflation. IL debt issuance is countercyclical, increases in periods of nominal exchange rate depreciations, and substitutes foreign currency (FC) and non-indexed local currency debt. A two-sector small-open economy model of public debt composition can deliver the business-cycle properties of IL debt and shows that, during crises, amid nominal exchange rate depreciations, IL debt becomes cheaper to issue. The study finds evidence of IL rates decreasing in about half of the most recent crises in emerging economies. Finally, the study compares IL rates to FC and LC rates and concludes that, for some countries, IL rates are below LC rates, even after accounting for expected inflation.